(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
Young people born between 1997 and 2012 grew up communicating across platforms where the boundary between speaking and writing barely exists - and their language reflects that. This paper examines 110 English slang expressions in active use between 2020 and 2025, tracing how they work, what they mean, and what social work they do for the people who use them. Most existing research treats podcast speech and social media writing as separate objects; this study treats them as two channels of the same phenomenon. The corpus was drawn from three English-language podcasts and cross-checked against TikTok, where each expression was verified across a minimum of ten independent videos before inclusion. Applying corpus methods alongside semantic and functional analysis, the study identifies twelve categories of slang. Emotional and reactive expressions account for the largest share at 13.6%; nine further categories - among them cross-platform slang, meme constructions, viral expressions, and clipped forms - each represent 9.1% of the corpus. What emerges from the analysis is that slang does considerably more than provide informal alternatives to standard vocabulary. It marks who belongs to a group, encodes emotional reactions in compact form, frames social judgments, and ties speakers to the broader landscape of popular culture. Platforms like TikTok appear to be accelerating how quickly new expressions spread and stabilize - a process with real consequences for how we understand language change in the digital age, and for how contemporary English might be taught to language learners.